Equine metabolic syndrome: Role of the enteroinsular axis in the insulin response to oral carbohydrate. (April 2023) - de Laat, Melody A.; Fitzgerald, Danielle M.
Abstract: Equine insulin dysregulation (ID) comprises amplified insulin responses to oral carbohydrates or insulin resistance, or both, which leads to sustained or periodic hyperinsulinaemia. Hyperinsulinaemia is important in horses because of its clear association with laminitis risk, and the gravity of this common sequela justifies the need for a better understanding of insulin and glucose homoeostasis in this species. Post-prandial hyperinsulinaemia is the more commonly identified component of ID and is diagnosed using tests that include an assessment of the gastrointestinal tract (GIT). There are several factors present in the GIT that either directly, or indirectly, enhance insulin secretion from the endocrine pancreas, and these factors are collectively referred to as the enteroinsular axis (EIA). A role for key components of the EIA, such as the incretin peptides glucagon-like peptide-1 and 2, in the pathophysiology of ID has been investigated in horses. By comparison, the function (and even existence) of many EIA peptides of potential importance, such as glicentin and oxyntomodulin, remains unexplored. The incretins that have been examined all increase insulin responses to oral carbohydrate through one or more mechanisms. This review presents what is known about the EIA in horses, and discusses how it might contribute to ID, then compares this to current understanding derived from the extensive studies undertaken in other species. Future directions for research are discussed and knowledge gaps that should be prioritised are suggested. Highlights: The connection between the gut and the pancreas is called the enteroinsular axis. The enteroinsular axis contributes to insulin dysregulation in horses. The incretins increase insulin responses to oral carbohydrate. Many potentially important enteroinsular peptides remain unexplored in horses.